A review on challenges, recent progress and applications of silica nanoparticles based superhydrophobic coatings. Issue 5 (1st March 2022) - Sharma, Konica; Hooda, Amrita; Goyat, M.S.; Rai, Radheshyam; Mittal, Ajay
Abstract: Over the past few decades, the study of superhydrophobic coatings (SHCs) gained the significant interest of worldwide researchers due to their tremendous applications in various sectors including, the metal industry, membrane industry, automation, structures, marine, defense, and medicines. The literature is full of review papers on the basics of SHCs, their synthesis methods, and their applications. But, minimal reviews are available on silica nanoparticles-based SHCs. However, silica nanoparticles are well-known material for SHCs due to their abundance, economical, transparency and ease of surface modification by various surface-functionalizing agents compared to other nanomaterials. Furthermore, silica nanoparticles are the most preferred material for the generation of nano-level roughness in the coatings to exhibit superhydrophobicity. Therefore, there is a great need to work in this direction. This work is dedicated to the challenges, recent progress and applications of silica nanoparticles-based superhydrophobic coatings.